Identification of a novel intronic variant in COL4A2 gene associated with fetal severe cerebral encephalomalacia and subdural hemorrhage - Rong-Yue Sun; Yue Xu; Qing-Qing Huang; Si-Si Hu; Hua-Zhi Xu; Yan-Zhao Luo; Ting Zhu; Jun-Hui Sun; Yu-Jing Gong; Mian-Mian Zhu; Hong-Wei Wang; Jing-Ye Pan; et al. (BMC, 2024)
Abstract Background Genetic variants in COL4A2 are less common than those of COL4A1 and their fetal clinical phenotype has not been well described to date. We present a fetus from China with an intronic variant in COL4A2 associated with a prenatal diagnosis of severe cerebral encephalomalacia and subdural hemorrhage. Methods Whole exome sequencing (WES) was applied to screen potential genetic causes. Bioinformatic analysis was performed to predict the pathogenicity of the variant. In in vitro experiment, the minigene assays were performed to assess the variant's effect. Results In this proband, we observed ventriculomegaly, subdural hemorrhage, and extensive encephalomalacia that initially suggested cerebral hypoxic-ischemic and/or hemorrhagic lesions. WES identified a de novo heterozygous variant c.549 + 5G > A in COL4A2 gene. This novel variant leads to the skipping of exon 8, which induces the loss of 24 native amino acids, resulting in a shortened COL4A2 protein (p.Pro161_Gly184del). Conclusion Our study demonstrated that c.549 + 5G > A in COL4A2 gene is a disease-causing variant by aberrant splicing. This finding enriches the variant spectrum of COL4A2 gene, which not only improves the understanding of the fetal neurological disorders associated with hypoxic-ischemic and hemorrhagic lesions from a clinical perspective but also provides guidance on genetic diagnosis and counseling.